Control of Blackpod Disease of Cocoa Using Leaf Extract of Ocimum gratissimum L. - Owusu-Ansah, Ernest; Oppong-Boachie, F.K.; Awuah, R.T. (Asian Journal of Chemistry, 2016)
The leaves of Ocimum gratissimum are characterized by strong aromatic odour and are used for the treatment of stomach disorders, sores and catarrh. Essential oil from the leaves, by steam distillation, gave four fractions upon column chromatography. Only the second fraction which is proven to be thymol by spectroscopic studies (IR and NMR) competed favourably in the suppression of the growth of Phytophthora palmivora, a pathogen that causes blackpod disease in cocoa pods with the crude essential oil in in vivo studies.